BETWEEN LEGAL NORMS AND ARGUMENTATION: THE THEORETICAL DIMENSION IN JUDICIAL DECISIONS: DIMENSIÓN TEÓRICA EN FALLOS JUDICIALES (ESMAT Magazine, 2025)
This article analyzes, from a qualitative approach, the evolution of Paraguayan jurisprudence from a theoretical and practical perspective, focusing on the transition from normative positivism to more argumentative interpretive models oriented toward legal principles. The main objective is to analyze the evolution of judicial practice toward argumentative justice based on principles, axiological weighing, and practical rationality. This objective is achieved through selected paradigmatic rulings of the Supreme Court of Justice, which examine how judges have begun to incorporate axiological and constitutional grounds into their decisions, moving beyond the mere mechanical application of the law by integrating contemporary theoretical foundations such as neoconstitutionalism, garantismo, Robert Alexy's theory of principles, and legal realism. The study of paradigmatic cases shows the construction of a more rights-based legal culture oriented toward substantive justice, where judicial decisions are based on judicial reasoning, coherent motivation, and the protection of fundamental rights. It concludes that Paraguayan jurisprudence is undergoing a process of transformation and consolidation toward a more rational, argumentative judicial interpretation committed to fundamental rights.
Keywords: Paraguayan Jurisprudence; Legal Theory; Neoconstitutionalism; Legal Argumentation; Constitutional Principles